Laparoscopic adrenalectomy - De Vinatea, José (2005)
Objective: To determine the effectiveness and results of laparoscopic adrenalectomy in the treatment of benign adrenal pathology. Materials and Methods: Clinical characteristics and outcomes of 15 laparoscopic adrenalectomies performed at both Guillermo Almenara Irigoyen National Hospital EsSalud and Clínica San Pablo, Lima – Peru, from 1996 to 2005 were determined, considering tumor size, surgical techniques and others. Results: Eleven unilateral and two bilateral adrenalectomies were indicated for non-functional adenoma (2), functional adenoma (6), pheochromocytoma (3), teratoma (1), myelolipoma (2), and leiomyosarcoma (1). There was no mortality or reoperations. Conclusion: Laparoscopic adrenalectomy for less than 7 cm benign adrenal tumors is recommended.